Pengaruh Kecerdsan Emosional dan Kepercayaan Diri Terhadap Personal Value Serta Dampaknya Terhadap Pemahaman Akuntansi Keuangan - Yuli Anwar (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2011)
The purpose of this study is to examine and analyze empirically the influence ofemotional quality, self confidance, and personal value, toward to understanding of financial accounting. Respondents in this study were use lecturer at privateuniversity in Bogor. The analysis used in this study using path analysis model, which is a method that uses exogenuous and endogenuous variables. Equation models in this study using two models, (1) equation of sub structural one, such as PV= β1KE1+ β2KD2 + ε1 and equation of sub structural two, such as PA = β1KE1+ β2 KD 2 + β3PV3 +ε2. The finding of this study substructural one that there is a direct influence and positive significant between emotional quality on personal value amounted to 0,345 (34,5%) and self confidence of 0,526 (52,60%). Meanwhile, the substructural two found that there is direct influence and positive significant between emotional quality on the understanding of financial accounting is 0,144 (14.40%) and self confidence to the understanding of financial accounting is 0,197 (19,70%), as well as the indirect effect positive emotional quality by considering personal value to the understanding of financial accounting is 0,383 (38,30%), as well as the indirect effect positive self confidence by considering the personal value to the understandingm of financial accounting is 0,561 (56,10%).Keyword: emotional quality, self confidence, personal value, understanding offinancial accounting